Affect Sharia Compliance and Exchange on the Balance of Payment Insurance Deficit in Indonesia - Dewi Tradena; Ruslan Abdul Ghofur; Erike Anggraini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Annual balance of payments insurance which has increased. An increase in the balance of payments deficit, if not immediately addressed, will have a negative impact on the country's economy and hinder the country's development and ultimately prosperity will be difficult to achieve. The purpose of this study was to examine the effect of financial performance, total sharia reinsurance assets, sharia compliance and exchange rates on the insurance balance of payments deficit in Indonesia. The method used in this research is quantitative research with the data used is secondary data in the form of time series obtained from the Financial Services Authority. Data collection uses documentation, in the form of quarterly data starting from 2010Q1-2019Q4. The total sample in this study was 40 research samples. The collected data were analyzed using multiple linear regression. The test instrument used was the SPSS IBM 21. This study shows that simultaneously financial performance, total sharia reinsurance assets, sharia compliance and the exchange rate have a significant effect on the insurance balance of payments deficit in Indonesia with a significance of 0.000. while the results of the partial test show that financial performance, total assets of sharia reinsurance, sharia compliance negatively affect the insurance balance of payments deficit in Indonesia. Meanwhile, the exchange rate has a significant and positive effect on the insurance balance of payments deficit in Indonesia. The coefficient of determination of Adjusted R^2 is 0.610 or 61%. That is, the ability of the independent variables namely financial performance variables, total assets, sharia compliance and the exchange rate in explaining the dependent variable, namely the Indonesian insurance balance of payments deficit for the 2010-2019 period is 61% and the remaining 49% is influenced by other variables outside the model that are not the study of this research. . Keywords; Balance of Payments Deficit, Exchange Rate, Sharia Compliance